Patterns of errors in the Swedish of Polish learners: Evidence from written Swedish - Malecza, Elżbieta (Wydawnictwo Naukowe UAM, 1992)
The author analyses the most typical errors in the Swedish of Polish learners. The analysis has been restricted to accounting for patterns which can be explained by negative interlingual interference. The errors have been divided into two groups: structural and lexico-semantic and supplied with numerous examples drawn from compositions and written exercises of various types of Polish learners. Errors in patterns of communicative competence are also dealt with. The analysis has been carried out in a traditional way and the emphasis has been put on its practical value.